Leadership Styles as A Moderating Variable Between Emotional Intelligence and Organizational Performance Among Cabuyao City Public Schools - Froilan H Bambico (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
This study examined whether leadership styles moderate the relationship between emotional intelligence (EI) and organizational performance among public school leaders in Cabuyao City. Emotional intelligence, encompassing self-awareness, self-management, social awareness, and relationship management, is widely recognized as a critical leadership competency influencing decision-making and interpersonal effectiveness. A descriptive-correlational research design was employed, utilizing adapted standardized instruments to measure emotional intelligence, leadership styles (transformational, democratic, visionary, and laissez-faire), and organizational performance based on the Office Performance Commitment and Review Form (OPCRF). Data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis to test moderation effects. Findings revealed that school leaders demonstrated very high levels of emotional intelligence and leadership styles, with transformational leadership ranking highest. Organizational performance was also high, with the majority of schools rated as “Outstanding” or “Very Satisfactory.” However, no significant relationship was found between emotional intelligence and organizational performance. Furthermore, leadership style did not significantly moderate this relationship. These results suggest that while emotional intelligence enhances leadership behavior, it may not directly translate into measurable organizational performance outcomes without the influence of contextual factors such as organizational culture, external demands, and institutional constraints. The study recommends targeted leadership development programs focusing on integrating emotional intelligence with strategic leadership practices.